Imitative and Creative Reasoning Abilities Viewed from Locus of Control on Guided Inquiry Model React Strategy - Sari, Niken Ramandha Wulan; Asikin, Mohammad; Mulyono, Mulyono (Universitas Negeri Semarang, 2020)
The aims of this study were (1) to know the quality of guided inquiry learning with REACT strategy on imitative and creative reasoning abilities, (2) to describe imitative and creative reasoning abilities viewed by internal locus of control on guided inquiry models REACT strategy, and (3) to describe imitative and creative reasoning abilities viewed by external locus of control on guided inquiry model REACT strategy. This study was a mixed method research with using convergent design. The population was 7th grade students of SMP N 3 Ungaran academic year 2017/2018. The subjects was selected based on internal locus of control and eksternal locus of control. The result showed that (1) guided inquiry learning with REACT strategy towards imitative and creative reasoning abilities was on good quality, (2) imitative and creative reasoning abilities of internal locus of control students can be achieved well, (3) imitative reasoning abilities of external locus of control students can be achieved well on indicators bearing in mind the facts, definitions and formulas used, while other indicators have not been achieved, student’s creative reasoning ability of external locus of control can be achieved well on indicators explaining the reasons for selection procedures . By knowing the locus of control of students, the teacher can design a learning model that is appropriate to the circumstances of the students. The existence of a guided inquiry learning model REACT strategy can train student’s imitative and creative reasoning abilities.